Metallo-beta-lactamases (MBLS) Producing Pseudomonas aeruginosa in Hospitalized Patients: An Increasing Threat in Tertiary Care Hospitals - Amit Singh; Sarita Sinha (Research Advances in Microbiology and Biotechnology Vol. 9, 2024)
This chapter aimed to detect the prevalence of MBLs in isolates of imipenem resistant P. aeruginosa from various inpatient departments and to determine the best phenotypic test for detection of MBLs. Pseudomonas aeruginosa is a Gram-negative pathogen that has become an important cause of infection in humans and can be associated with significant morbidity and mortality. Infections acquired in connection with hospitalization can lead to significant morbidity and mortality, but preventive anti-infective measures can significantly affect these result. It was a prospective observational study conducted at Department of Microbiology, Uttar Pradesh University of Medical Sciences, Saifai, Etawah, UP, India. All the sample from June 2016-2017 of one year were processed for the study. A total of 14700 samples were screened for P. aeruginosa by conventional culture and biochemical tests. All confirmed P. aeruginosa isolates were further subjected to Modified Kirby- Bauer disc diffusion test as per CLSI guidelines. All IPM resistant isolates were screened for MBL production by DDST, CDST, MHT and E-test MBL. A total of 1423 were identified as P. aeruginosa. The isolation rate of P. aeruginosa at our hospital was 9.7%. Among these, 130(9.1%) isolates were IPM resistant. A total of 111 (85.4%) were MBL positive by CDST and E-test, 92 (70.5%) by DDST and 80 (61.5%) by MHT. Metallo-beta-lactamase producing Pseudomonas aeruginosa is an important nosocomial pathogen that shows resistance to all beta-lactam antibiotics except monobactams. Present study shows a quite alarming 85% MBL positive imipenem resistant Pseudomonas aeruginosa cases. This study found imipenem-EDTA combine disc test detected more MBLs isolates, than combined disc test, according to E-test for MBLs 111 out of 130 had ratio >8 and were confirmed as MBL-producing isolates.